Analisis Penggunaan Kalimat Bahasa Indonesia pada Karangan Siswa Kelas V Sekolah Dasar Negeri 10 Sanur, Denpasar - Yuni Antari, Wayan; Sri Satyawati, Made (Humanis; Vol 21 No 1 (2017), 2017)
This research entitled "Analysis of the Use of Indonesian Sentences in the Essay of Students Class V SDN 10 Sanur, Denpasar". The purpose of this research is to contribute a donation to the results of thought in the field of linguistics. The method that used to collect data in this research is the method of observation (observasi), then the data is analyzed by qualitative descriptive method, quantitative method, and distribution method (agih). Method of presentation of result of data analysis that used is formal method and informal method. Sources of data in this research is the essay of students of class V SDN 10 Sanur, Denpasar a total of 68 essays. The student of the class V is a student class V period of 2016/2017. The base of theory that used in this research is the syntactic theory according to Verhaar (1990), sentence theory according to Alwi et al. In standard Indonesian grammar, effective sentence theory according to Widjono (2012), and theory of language error according to Tarigan. The results of this research that is the type of sentence contained in the essay of students class V SDN 10 Sanur, Denpasar is distinguished by the total of clauses and forms, that is single sentence in the form of single sentence by verbal predicate, single sentence by adjektival predicate, equivalent compound sentence, multi-tiered sentences, declarative sentences , Imperative sentences, interrogative sentences, and exclamative sentences. Second, in the sentence of the student of class V SDN 10 Sanur, Denpasar found elements that filled a function,  a category, and the role of syntax. Third, the sentence errors in the essays of students of class V SDN 10 Sanur, Denpasar are divided into three types, namely sentence structure sentences of 136 sentences (16.4%), 181 sentence (dictionary) word error (21.8%), and spelling errors. A total of 268 sentences (32.3%). The total percentage of sentence errors overall is 70.5%.